Tuning the semimetallic charge transport in the Weyl semimetal candidate Eu2Ir2O7 (111) epitaxial thin film with an all-in-all-out spin structure. (20th April 2022) - Ghosh, Mithun; Bhat, Shwetha G; Pal, Anand; Kumar, P S Anil
Abstract: We report the stoichiometric epitaxial growth of the Eu2 Ir2 O7 (111) thin film on YSZ substrate by a two-step solid phase epitaxy (SPE) method. An optimized post-annealing environment of the SPE was superior over the conventional air annealing procedure to get rid of the typical impurity phase, Eu2 O3 . The thickness-dependent structural study on Eu2 Ir2 O7 (111) thin films suggests a systematic control of Ir/Eu stoichiometry in our films, which is otherwise difficult to achieve. In addition, the low-temperature electrical resistivity studies strongly support the claim. The power-law dependence analysis of the resistivity data exhibits a power exponent of 0.52 in 50 nm sample suggesting possible disorder-driven semimetallic charge transport in the 3D Weyl semimetallic (WSM) candidate Eu2 Ir2 O7 . In addition, the all-in-all-out/all-out-all-in antiferromagnetic domains of Ir 4+ sublattice is verified using the field cooled magnetoresistance measurements at 2 K. Hall resistivity analysis indicate semimetallic hole carrier type dominance near the Fermi level up to the measured temperature range of 2–120 K. Altogether, our study reveals the ground state of stoichiometric Eu2 Ir2 O7 (111) thin film, with an indirect tuning of the off-stoichiometry using thickness of the samples, which is of interest in the search of the predicted 3D WSM phase.